EFEKTIFITAS PENYULUHAN PADA IBU HAMIL UNTUK MENINGKATKAN PENGETAHUAN TENTANG POST PARTUM BLUES DI KELURAHAN TAMBUSAI TENGAH - Nainggolan, Enny Suwita; Fitria, Rahmi; Sulistiawati, Wiwin; Nasriyah, Isom; Nurmawilis, Nova (AHM Center, 2025)
Postpartum blues until now the cause is not known with certainty. However, in several studies, postpartum blues was influenced by external factors including socioeconomic status and unfavorable economic conditions. One of the internal factors that play a role in postpartum blues is changes in hormone levels and the age factor that is associated with this problem. Being too young to get pregnant poses a risk to both mother and child physically and psychologically both during pregnancy and childbirth. The purpose of this study was to determine the effect of counseling in increasing pregnant women's knowledge about postpartum blues in Tambusai Tengah Village. This research method is quantitative analytic with the research design used is pre-experimental with one group pre-test and post-test design. Data collection used primary data using a questionnaire which was filled in during counseling, while data analysis used the T-Dependent test. The population of this study were all pregnant women in the Central Tambusai Village. The sample in this study was 32 pregnant women. The results of this study obtained that the average knowledge before being given counseling was 10.28 ± 3.3. While knowledge after being given counseling 17.58 ± 2.4. The results of the statistical test obtained a value of p = 0.000, which means that there is an influence of counseling in increasing the level of knowledge of pregnant women about postpartum blues. The conclusion is that there is a significant effect (p value = 0.00), which means that there is a significant effect on increasing knowledge before and after being given counseling.